Implementation of Job Rotation as an Effort to Strengthen Sustainable Business Performance - Apriyanto, Apriyanto; Priyana, Yana; Badriyah, Siti; Budiman, Dana (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study explores the implementation of job rotation as a strategic tool to enhance sustainable business performance. Using a quantitative approach, data was collected from 100 respondents through a structured Likert-scale questionnaire. The study focuses on how job rotation influences key organizational elements such as employee development, work motivation, and adaptability, all of which are crucial for achieving sustainable performance. The data was analyzed using SPSS version 25, including descriptive statistics, validity and reliability testing, and simple linear regression. The findings indicate a positive and significant relationship between job rotation and sustainable business performance, with a regression coefficient of 0.712 and a significance value of 0.000. The coefficient of determination (R²) of 0.552 suggests that job rotation accounts for 55.2% of the variance in sustainable business performance. This highlights the substantial role job rotation plays in improving long-term organizational sustainability. Additionally, the study provides practical implications for managers, urging them to design job rotation programs that align with organizational objectives and employee development needs. By doing so, companies can foster a more adaptable, motivated, and skilled workforce, which in turn supports the sustainability of their business performance. Furthermore, the study emphasizes the importance of aligning job rotation practices with strategic human resource management efforts to maximize their impact on organizational sustainability. These findings contribute to the broader understanding of human resource management practices and their role in fostering long-term business success.